Novel CYP24A1 Mutation in a Young Male Patient with Nephrolithiasis: Case Report - Jana Jiráčková; Radomir Hyšpler; Sumaya Alkanderi; Ladislava Pavlíková; Vladimir Palicka; John A. Sayer (Karger Publishers, 2019)
Background/Aims: The CYP24A1 gene encodes the vitamin D 24-hydroxylase enzyme, which hydroxylates active forms of vitamin D into inactive forms. Biallelic mutations in the CYP24A1 gene can lead to elevated levels of active vitamin D metabolites and, consequently, to hypercalcemia, hypercalciuria, nephrocalcinosis, and nephrolithiasis; however, monoallelic mutations have been associated only with milder phenotypes. In the present manuscript, we report the case of a young male patient who presented hypercalcemia and nephrolithiasis, suppressed parathormone, and elevated 1,25 dihydroxy vitamin D levels. Methods: Biochemical analyses were performed on Cobas 8000, F. Hoffmann-La Roche AG, Basel, Switzerland. The proband was initially evaluated for occult malignancies by body imaging, serum electrophoresis, and tumor markers, which did not reveal any pathology. DNA samples of the proband and his sibling were then examined using Sanger sequencing. Results: Genetic analysis revealed 2 compound heterozygous CYP24A1 mutations (p.L148P and p.R223*). The novel nonsense CYP24A1 mutation, p.R223*, was also found heterozygously in other family members with a medical history of nephrolithiasis. Conclusions: The identification of this gene mutation causing hypercalcemia, hypercalciuria, and renal stones allows the specific management of endogenous vitamin D production.